2006
DOI: 10.1051/parasite/2006134267
|View full text |Cite
|
Sign up to set email alerts
|

Hemolivia mauritanica(Haemogregarinidae: Apicomplexa) infection in the tortoiseTestudo graecain the Near East with data on sporogonous development in the tick vectorHyalomna aegyptium

Abstract: Summary :Testudo graeca tortoises were collected in the northern and southern Golan Heights (Israeli occupied territory of south Syria), and various locations in Israel and Palestine. Hyalomma aegyptium ticks were found only on Golan Height tortoises, and only the tortoises and ticks from the northern Golan Heights were infected with Hemolivia mauritanica. Tortoises became infected after ingesting infected ticks. Male ticks carrying sporocysts, which remain attached to tortoises for extended durations, apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“… Hyalomma spp. Pathogens list I # Pathogens list II ## H. aegyptium Theileria annulata ( Ray, 1950 ) Hepatozoon kisrae ( Paperna et al., 2002 ) Hemolivia mauritanica ( Paperna, 2006 ) Coxiella burnetii ( Siroký et al., 2010 ) Anaplasma phagocytophilum and Ehrlichia canis ( Pastiu et al., 2012 ) Borrelia turcica Sp. Nov. ( Güner et al., 2004 ) Borrelia burgdorferi s.l.…”
Section: Impact Of Hyalomma Ticks On Animalsmentioning
confidence: 99%
“… Hyalomma spp. Pathogens list I # Pathogens list II ## H. aegyptium Theileria annulata ( Ray, 1950 ) Hepatozoon kisrae ( Paperna et al., 2002 ) Hemolivia mauritanica ( Paperna, 2006 ) Coxiella burnetii ( Siroký et al., 2010 ) Anaplasma phagocytophilum and Ehrlichia canis ( Pastiu et al., 2012 ) Borrelia turcica Sp. Nov. ( Güner et al., 2004 ) Borrelia burgdorferi s.l.…”
Section: Impact Of Hyalomma Ticks On Animalsmentioning
confidence: 99%
“…Such routes are well known for other tick-borne haemoprotozoans, such as Hepatozoon canis or H. americanum which are transmitted to dogs following ingestion of infected Rhipicephalus [20], Haemaphysalis [21] and Amblyomma [22][23][24] ticks. Apicomplexans of the genus Hemolivia are also known to be transmitted via tick ingestion to their vertebrate hosts [25][26][27][28]. These routes of transmission seem to represent evolutionary adaptations related to the feeding habits of the vertebrate hosts [29].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that during its life cycle, this species uses two or three different host species (OBA;SCHUMAKER, 1983;RODRIGUES et al, 2010). In addition, ticks can act as vectors of hemoparasites of the genera Hemolivia and Hepatozoon for frogs (PETIT et al, 1990;LAINSON et al, 2007), lizards (SMALLRIDGE;PAPERNA, 1997;PAPERNA et al, 2002) and turtles (PAPERNA, 2006;SIROKÝ et al, 2009).…”
Section: Introductionmentioning
confidence: 99%